1996
DOI: 10.1128/jb.178.22.6644-6646.1996
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of pyridine nucleotide-disulfide oxidoreductase is essential for NAD+- and NADPH-dependent degradation of epoxyalkanes by Xanthobacter strain Py2

Abstract: Epoxide degradation in cell extracts of Xanthobacter strain Py2 has been reported to be dependent on NAD ؉ and dithiols. This multicomponent system has now been fractionated. A key protein encoded by a DNA fragment complementing a Xanthobacter strain Py2 mutant unable to degrade epoxides was purified and analyzed. This NADP-dependent protein, a novel type of pyridine nucleotide-disulfide oxidoreductase, is essential for epoxide degradation. NADPH, acting as the physiological cofactor, replaced the dithiols in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…This proposal is strengthened by the recent identification of component II as an NADPH:disulfide oxidoreductase (12). Interestingly, in the absence of CO 2 , epoxide carboxylase catalyzes the isomerization of aliphatic epoxides to form ketones at rates comparable to those observed for carboxylation (4,9) as shown in Equation 3.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…This proposal is strengthened by the recent identification of component II as an NADPH:disulfide oxidoreductase (12). Interestingly, in the absence of CO 2 , epoxide carboxylase catalyzes the isomerization of aliphatic epoxides to form ketones at rates comparable to those observed for carboxylation (4,9) as shown in Equation 3.…”
mentioning
confidence: 69%
“…The sequence of this DNA fragment revealed four ORFs, designated orf1, orf2, orf3, and orf4, that may represent one or more of the components of the epoxide carboxylase system (16). Analysis of the molecular weight, N-terminal sequence, and amino acid composition of purified component II revealed that this protein corresponded to orf3 of the complementary DNA fragment (11,12). To determine whether the three epoxide carboxylase components purified in this study correlate with any of the remaining ORFs, the molecular weights, N-terminal sequences, and amino acid compositions of purified components I, III, and IV were determined (Tables V and VI).…”
Section: Analysis Of N-terminal Sequences and Amino Acid Compositionsmentioning
confidence: 99%
See 3 more Smart Citations